The primal garden: Tajikistan as a biodiversity hotspot of food crop wild relatives - Kotowski, Marcin; Świerszcz, Sebastian; Khoury, Colin K.; Laldjebaev, Murodbek; Palavonshanbeeva, Barfiya; Nowak, Arkadiusz (Springer, 2022)
Despite being located within a primary region of crop diversity, documentation of Tajik crop and crop wild relative (CWR) resources is far from comprehensive, particularly regarding CWR. Here, we compile the first inventory of food CWR of Tajikistan. A total of 549 food CWR taxa belonging to 36 families and 125 genera were documented as occurring in the country. Among them, 71 taxa were recognized as native close relatives of globally important crops (category 1A), 67 as native distant relatives of these crops (1B) and 411 as native taxa with an undetermined relationship to these crops (1C). This documented CWR diversity far exceeds previous scientific assessments for the country and, in doing so, distinguishes the Tajik region from surrounding countries. Within the country, the results indicate a clear gradient of food CWR taxonomic richness from the eastern part of the country (least diversity) to the western part (greatest diversity). This trend adds important new information to the body of literature published by N. I. Vavilov and others, who mainly stressed the importance of the Pamir region (Eastern Tajikistan) for crop and CWR diversity.